Risk-taking and pathological gambling behavior in Huntington’s disease - Kalkhoven, Carla E.; Sennef, Cor; Peeters, Ard; Van Den Bos, Ruud (Frontiers in Behavioral Neuroscience, 2014)
Huntington’s disease (HD) is a genetic, neurodegenerative disorder, which specifically affects striatal neurons of the indirect pathway, resulting in a progressive decline in muscle coordination and loss of emotional and cognitive control. Interestingly, predisposition to pathological gambling and other addictions involves disturbances in the same cortico-striatal circuits that are affected in HD, and display similar disinhibition-related symptoms, including changed sensitivity to punishments and rewards, impulsivity, and inability to consider long-term advantages over short-term rewards. Both HD patients and pathological gamblers also show similar performance deficits on risky decision-making tasks, such as the Iowa Gambling Task (IGT). These similarities suggest that HD patients are a likely risk group for gambling problems. However, such problems have only incidentally been observed in HD patients. In this review, we aim to characterize the risk of pathological gambling in HD, as well as the underlying neurobiological mechanisms. Especially with the current rise of easily accessible Internet gambling opportunities, it is important to understand these risks and provide appropriate patient support accordingly. Based on neuropathological and behavioral findings, we propose that HD patients may not have an increased tendency to seek risks and start gambling, but that they do have an increased chance of developing an addiction once they engage in gambling activities. Therefore, current and future developments of Internet gambling possibilities and related addictions should be regarded with care, especially for vulnerable groups like HD patients.